Review on Software Testing Model Approach for Efficient Bug Finding With Yin-Yang Testing Theory - Kumar, Mohit; Gandhi, Geetika; Garg, Sushil (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Model Selection for Software testing is very important prospective in various product accuracy. Through research on software testing model selection, seeking the most appropriate testing method to achieve most reasonable testing volume and optimal testing result. In our Research we will focus on improving this model description by adding more user end experience in acceptance testing. Various experiences from industrial companies will be fetched and will be implemented according to the optimized Yin-Yan Theory for software testing. We will also try to introduce more testing dependencies. In User testing, we will add offline and online dependencies test which will be helpful in finding issues in overall acceptance testing phase. Software testing will be done by various tools and will link to proposed theory. Test model selection and test volume evaluation method will be applied to the software testing work of Industrial applications and will compared with traditional method.